Demand Subsidies Versus R&D: Comparing the Uncertain Impacts of Policy on a Pre-Commercial Low-Carbon Energy Technology - Nemet, Gregory F.; Baker, Erin (My University, 2008)
To compare the effects of publicly sponsored research and development and subsidies for demand, the authors combine a bottom-up manufacturing cost model with information gathered from experts. They apply their model to purely organic photovoltatics, a low-carbon energy technology that is not commercially available, and find that successful R&D programs reduce costs more than demand subsidies. They also find that quality R&D brought the cost of the photovoltaics to 4 cents per kilowatt-hour, which subsidies alone could not achieve.